2012
DOI: 10.3892/ijo.2012.1456
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential prognostic biomarkers for node-negative breast tumours by proteomic analysis: A multicentric 2004 national PHRC study

Abstract: Abstract. We used a 2D-electrophoresis (2-DE) proteomic approach to identify novel biomarkers in node-negative breast cancers. This retrospective study focused on a population of patients with ductal pN0M0 tumours. A subset of patients who developed metastases and in whose tumours were found high levels of uPA and PAI-1 (metastatic relapse, MR: n=20) were compared to another subset in whom no metastatic relapse occurred and whose tumours were found to have low levels of uPA and PAI-1 (no relapse, NR: n=21). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Descotes et al used 2D-electrophoresis and Western blotting in 41 node-negative breast cancers of which 20 had metastatic relapse and 21 had no metastatic recurrence [6]. The former group had significantly higher GAPDH expression.…”
Section: Discussionmentioning
confidence: 99%
“…Descotes et al used 2D-electrophoresis and Western blotting in 41 node-negative breast cancers of which 20 had metastatic relapse and 21 had no metastatic recurrence [6]. The former group had significantly higher GAPDH expression.…”
Section: Discussionmentioning
confidence: 99%
“…GPD1L is one of the down‐regulated genes, and its function in tumours is not clear . Recently, Descotes et al . identified potential prognostic biomarkers for node‐negative breast tumours by proteomic analysis; their study found that GPD1, the homologous molecule of GPD1L, was differentially expressed, allowing prediction of tumour relapse.…”
Section: Discussionmentioning
confidence: 99%
“…GPD1L is one of the down-regulated genes, and its function in tumours is not clear. 3 Recently, Descotes et al 11 identified potential prognostic biomarkers for node-nega- Underlined values represent a statistically significant difference tive breast tumours by proteomic analysis; their study found that GPD1, the homologous molecule of GPD1L, was differentially expressed, allowing prediction of tumour relapse. In our study, decreased expression of GPD1L was quantitatively detected at the mRNA level in HNSCC tissues compared with adjacent normal tissues, suggesting that GPD1L may suppress initiation and development of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…25 Equally, addressing the same area with the help of MS technology demonstrated Ferritin light chain (FTL) as a potential biomarker in node negative breast cancer tissue. 26 In this multicentre study, Jezequel et al successfully validated the prognostic value of FTL where its overexpression was associated with a more aggressive phenotype in this subgroup of patients. In addition, this work demonstrated that FTL was stored in tissueassociated macrophages (TAM).…”
Section: Breast Cancer Prognosismentioning
confidence: 94%